Forecasting trends of the adult learner in higher education / - Lambert, Joanne Adam (My University, 1983)
Panelists expressed doubt that changes would be made in the physical environment of the institutions to accomodate the adult students. This concern might be related to the high expectations shown by the panel for increased adult part-time enrollment, indicating anticipated low demand for increased resident student accommodations.

The administrators involved in the study demonstrated that they were generally alert to the adult educational trends in higher education. Their opinions concerning the likelihood of occurrence for specified events and the comments they made regarding the predictions indicated a knowledge of happenings beyond their own institutional boundaries. They forecast a continued increase in adult participation in higher education and an accelerated rate of activity in nontraditional delivery systems; trends which were also indicated in the literature. They predicted that higher education institutions would adjust to the demands of the new student population through flexibility in scheduling of classes and services, and through simplification of enrollment procedures.

This study was conducted for the purpose of predicting future trends in adult enrollment in Oklahoma higher education institutions within the next 20 years, and institutional changes that may be expected to occur related to these trends. The Delphi technique was employed to collect data for the study from deans of students and directors of continuing education at Oklahoma higher education institutions.

Sixty administrators were identified as fulfilling necessary panelist requirements for the study. They were asked to respond to two categories of inquiry by listing (1) predicted adult enrollment trends in Oklahoma higher education, and (2) anticipated institutional changes; both within the next 20 years. Responses produced 272 statements which were synthesized into 45 items for consideration in the next rounds of questioning. Consensus was reached for all statements. Agreement in regard to the likelihood that the event would occur with any degree of certainty was indicated for 20 of the statements.
Keywords: Education, Adult and Continuing.